"I Didn't Choose This. It Chose Me." Community-Based Environmental Justice Leaders. (November 2020) - Mohai, Paul; Bryant, Bunyan; Slatin, Craig
On 13 February 2020, the University of Michigan School for Environment and Sustainability held the Michigan Environmental Justice Summit 2020: Commemorating the Thirtieth Anniversary of Michigan's 1990 Conference on Race and the Environment and Looking Toward the Future. The Summit hosted a dynamic panel of community environmental justice leaders throughout the region who have "boots on the ground" in the progress and pursuit of environmental justice. The panelists included Donele Wilkins, the President/CEO of the Green Door Initiative in Detroit, MI; Andrea Pierce, Chair and Founder of the Anishinaabek Caucus, Idle No More Michigan, MI; and Theresa Landrum, co-founder of the 48217 Community and Environmental Health Organization, Detroit, MI. This article includes an edited transcript of the panel discussion. The panelists detail multiple grassroots efforts to remedy environmental injustice in Michigan.